2015
DOI: 10.1121/1.4908308
|View full text |Cite
|
Sign up to set email alerts
|

Using speech sounds to test functional spectral resolution in listeners with cochlear implants

Abstract: In this study, spectral properties of speech sounds were used to test functional spectral resolution in people who use cochlear implants (CIs). Specifically, perception of the /ba/-/da/ contrast was tested using two spectral cues: Formant transitions (a fine-resolution cue) and spectral tilt (a coarse-resolution cue). Higher weighting of the formant cues was used as an index of better spectral cue perception. Participants included 19 CI listeners and 10 listeners with normal hearing (NH), for whom spectral res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 55 publications
5
59
0
1
Order By: Relevance
“…However, it is possible that some CI users might be able to utilize a different acoustic cue in the naturally produced speech stimuli in the training sessions to categorize the speech contrasts, limiting the success of our training program for some listeners. Winn and Litovsky (2015) recently examined the perceptual weighting of the formant transition and spectral tilt cues used to categorize the /ba/-/da/ contrast in CI users. Their results suggest that, unlike NH listeners, CI users tend to weight the spectral tilt, the balance of high versus low frequency information, more heavily than the formant transition cue when categorizing /ba/ versus /da/.…”
Section: Success and Limitations Of Trainingmentioning
confidence: 99%
“…However, it is possible that some CI users might be able to utilize a different acoustic cue in the naturally produced speech stimuli in the training sessions to categorize the speech contrasts, limiting the success of our training program for some listeners. Winn and Litovsky (2015) recently examined the perceptual weighting of the formant transition and spectral tilt cues used to categorize the /ba/-/da/ contrast in CI users. Their results suggest that, unlike NH listeners, CI users tend to weight the spectral tilt, the balance of high versus low frequency information, more heavily than the formant transition cue when categorizing /ba/ versus /da/.…”
Section: Success and Limitations Of Trainingmentioning
confidence: 99%
“…Although the difficulties experienced by CI users may be due to reduced spectral resolution, additional factors such as frequency-to-place mismatch, electrical channel interaction, and etiology of deafness also constrain speech intelligibility in CI recipients (Winn and Litovsky, 2015). These additional factors make it difficult to assess the contribution of spectral resolution alone.…”
Section: Introductionmentioning
confidence: 98%
“…Measures of spectral resolution, such as the traditional spectral ripple test (Henry & Turner 2003) or spectral tilt measures (Winn & Litovsky 2015), which do not rely on such learned associations, offer a solution to this problem. In general, it has been shown that better spectral resolution correlates with better speech recognition in noise for CI users (Drennan et al 2016; Henry & Turner 2003; Holden et al 2016; Won et al 2007; however, see Langner et al 2017).…”
Section: Introductionmentioning
confidence: 99%